Integrasi Sistem Pendaftaran melalui Platform Mobile JKN di RSUD. Daha Husada Kediri - Cici Nila Ardila; Anggia Dini Marsaroha Panggabean; Krisnita Dwi Jayanti; Eva Firdayanti Bisono; Luthfiana Nur (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Currently, BPJS Kesehatan is implementing digital transformation through the Mobile JKN application. This application is expected to provide easier access and improve the quality of services for participants. However, in practice, there are still challenges, one of which is the accuracy of staff in checking patient labels, which causes difficulties in identifying patient forms. This study aims to determine the implementation of the patient registration system through the Mobile JKN application at RSUD Daha Husada Kediri. The research used a descriptive design with a quantitative approach and employed simple random sampling involving 75 patients. at RSUD Daha Husada Kediri. The research used a descriptive design with a quantitative approach and employed simple random sampling involving 75 patients. Data were collected using questionnaires. The results showed that RSUD Daha Husada Kediri has established policies regarding the Medical Record Service Guidelines and Standard Operating Procedures (SOP) for Online Registration via Mobile JKN. The implementation of registration through Mobile JKN generally runs well, as indicated by 96% of the 75 samples being in accordance with the procedures. However, some discrepancies still occur, particularly in the stage where staff have not checked patient labels before printing the SEP. It is recommended that RSUD Daha Husada Kediri provide training and socialization for registration staff regarding the registration flow via Mobile JKN, as well as education for patients to understand the registration procedures according to the SOP, so that the implementation can be more orderly and optimal.